"who cares about us?" Results of a cross-sectional study on the psychosocial health of obstetricians and midwives after traumatic birth experiences "wer kümmert sich um uns?" Ergebnisse einer Querschnittsuntersuchung zur psychosozialen Gesundheit von Geburtshelfer*innen und Hebammen nach traumatischen Geburtserlebnissen - Hüner, Beate; Kehl, Sven; Stelzl, Patrick; Friedl, Thomas W.P.; Janni, Wolfgang; Reister, Frank; Lunkenheimer, Frederike (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Background: Traumatic births not only cause emotional stress for expectant parents but can also affect the psychosocial health of midwives and obstetricians due to their professional demands. Aim: To evaluate the impact of traumatic birth experiences on the psychosocial health of obstetric healthcare professionals. Methods: A cross-sectional study using validated measurement tools (Impact of Event Scale Revised IES-R, Copenhagen Burnout Inventory CBI) and assessing post-traumatic growth (PGI-SF) through an online survey of midwives and obstetricians in German-speaking areas. Results: The study included 700 participants with peripartum and/or personal traumas. Of the 528 participants who completed the IES-R, 33 (6.3%) with post-traumatic stress disorder (PTSD) received less support from colleagues (p = 0.007) and were more likely to experience workplace consequences (p < 0.001) than participants without PTSD. A moderate to high level of burnout was found in 66.2% of the 542 participants who completed the CBI. Personal growth through experiencing trauma was reported by 75.9% of the 528 participants who completed the PGI-SF. Conclusion: The psychosocial health of midwives and obstetricians is at risk due to traumatic birth experiences. Screening tests and the provision of collegial and professional debriefings to strengthen resilience are essential preventive interventions.
CRIS-Team Scopus Importer:2025-02-04
Keywords: communication; healthcare workers; post-traumatic stress disorder; traumatic childbirth